THE IMPACT OF FLIPPED CLASSROOM APPROACH ON THE WRITING ACHIEVEMENT AND SELF-REGULATED LEARNING OF PRE-SERVICE ENGLISH TEACHERS - Altas, Ezgi Aydemir; Mede, Enisa (ANADOLU UNIV, 2021)
The major purpose of this study is to investigate the impact of flipped classroom on pre-service English teachers' Advanced Writing achievement. The study also aims at exploring whether flipped classroom approach makes a difference, if any, on the self-regulated learning of the participants. The participants of this study were selected by convenience sampling method and consisted of fifty-five (N=55) pre-service ELT teachers attending Advanced Writing course and studying at English Language Teaching Department (ELT) at a foundation university in the fall semester of 2017-2018 academic year. Two intact classes were selected as control (N=28) and experimental group (N=27). The control group was exposed to traditional lecture based instruction, whereas the experimental group received the flipped classroom approach. In this quasi-experimental study, data were gathered through pre-post-tests of advanced writing and self-regulated learning scale. Mixed ANOVA analysis was used for data analysis. The obtained results demonstrated that the implementation of flipped classroom approach resulted in better writing achievement, yet self-regulated learning showed no significant difference between groups. Based on these findings, the study provides pedagogical implications and suggestions for integrating flipped classroom approach in the undergraduate programs.
Keywords: Flipped classroom approach; self-regulated learning; ELT; writing achievement; Education & Educational Research